KEBIJAKAN DANA DESA DALAM MENUNJANG PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT PERDESAAN PADA DESA PANIKEL KECAMATAN KAMPUNG LAUT KABUPATEN CILACAP - Hidayah, Tofik Wahyu (Magister Manajement Studies Program, 2023)
This research is entitled VILLAGE FUND POLICY IN SUPPORTING RURAL COMMUNITY DEVELOPMENT AND EMPOWERMENT IN PANIKEL VILLAGE, KAMPUNG LAUT DISTRICT, CILACAP REGENCY. The Village Fund Budget which is sourced directly from the State Revenue and Expenditure Budget which has been distributed to Panikel Village from 2015 to 2021 is already quite large . However, in its utilization it has not been able to be utilized optimally for the welfare of the community. This is measured by the portion of Village Original Income to Village Income in the Village Revenue and Expenditure Budget which is still very small. This shows that the level of village independence is still very lacking and is still very dependent on transfer income and financial assistance. The method used in this research is a descriptive approach with a qualitative approach, the results of the study 1) The Village Fund Policy has been implemented well, although the results have not been effective. The policy has been implemented well, seen from infrastructure development activities as well as the implementation of community development and empowerment. It has not been effective because if it is measured from the portion of Village Original Income to total village income for one year it is still relatively small. 2) Utilization of Village Funds for 2021 cannot be maximized for community development and empowerment. This is because for 2021, based on priorities, it is used for handling the Covid-19 pandemic in villages